Reduction of microbial contamination and biogenic amines formation in Ras cheese using Chlorella vulgaris extracts - Diaa A. Marrez (Biotechnology Reports)
The present study aimed to explore the impact of C. vulgaris aqueous and diethyl ether extracts on reducing microbial contamination and biogenic amines (BAs) formation in Ras cheese during ripening process. Phenolic profile of aqueous extract was quantified by high performance liquid chromatography (HPLC) and compounds in ether extract were determined using gas chromatography-mass spectrometry (GC–MS). Eleven compounds were detected in aqueous extract and catechin was the major (54.82 µg/g), while 14 compounds were detected in ether extract of which the main compounds hexadecane (14.26 %) and 9, 12-Octadecadienoic acid, methyl ester (9.61 %). C. vulgaris aqueous and ether extracts observed antibacterial activity against seven strains of foodborne bacteria with minimum inhibitory concentration (MIC) ranged from 0.33 to 1.43 mg/mL and antifungal activity against 9 strains of toxigenic fungi with MIC values from 0.42 to 1.74 mg/mL. Ras cheese treated with ether extract had the highest reduction in formation of tryptamine (93.4 %), β-phenylethylamine (86.4 %), Putrescine (88.3 %), Cadaverine (81.8 %), Histamine (62.9 %), Serotonin (92.1 %), Tyramine (87.2 %), Spermidine (80.8) and Spermine (86.8 %) compared to cheese treated with aqueous extract and control samples. Also, the microbial load (total bacterial count, yeasts and molds count, proteolytic bacterial count) in Ras cheese samples treated with C. vulgaris aqueous and diethyl ether extracts were lower than the control sample. Whereas, no growth of coliform group, Staphylococci and Salmonella were detected in treated samples and control. The microalga C. vulgaris extracts considered promising source from natural ingredients to reduce biogenic amines content and microbial load in cheese manufacturing.